Control of Staphylococcus aureus Quorum Sensing by a Membrane-Embedded Peptidase - Cosgriff, Chance J. (Infect Immun, 2019)
Gram-positive bacteria process and release small peptides, or pheromones, that act as signals for the induction of adaptive traits, including those involved in pathogenesis. One class of small signaling pheromones is the cyclic autoinducing peptides (AIPs), which regulate expression of genes that orchestrate virulence and persistence in a range of microbes, including staphylococci, listeriae, clostridia, and enterococci. In a genetic screen for Staphylococcus aureus secreted virulence factors, we identified an S. aureus mutant containing an insertion in the gene SAUSA300_1984 (mroQ), which encodes a putative membrane-embedded metalloprotease. A ΔmroQ mutant exhibited impaired induction of Toll-like receptor 2-dependent inflammatory responses from macrophages but elicited greater production of the inflammatory cytokine interleukin-1β and was attenuated in a murine skin and soft tissue infection model. The ΔmroQ mutant phenocopies an S. aureus mutant containing a deletion of the accessory gene regulatory system (Agr), wherein both strains have significantly reduced production of secreted toxins and virulence factors but increased surface protein A abundance. The Agr system controls virulence factor gene expression in S. aureus by sensing the accumulation of AIP via the histidine kinase AgrC and the response regulator AgrA. We provide evidence to suggest that MroQ acts within the Agr pathway to facilitate the optimal processing or export of AIP for signal amplification through AgrC/A and induction of virulence factor gene expression. Mutation of MroQ active-site residues significantly reduces AIP signaling and attenuates virulence. Altogether, this work identifies a new component of the Agr quorum-sensing circuit that is critical for the production of S. aureus virulence factors.